Formation of NiO and Ni in an Aqueous Solution Using Plasma Discharge Electrolysis. Issue 12 (1st January 2019) - Shen, Lingling; Kong, Lingqiang; Zhao, Bo; Feng, Sen; Liu, Aimin; Xu, Junli; Boča, Miroslav; Shi, Zhongning
Abstract : NiO and Ni powders were prepared using plasma discharge electrolysis from NiSO4  solution and NiSO4 –NiCl2  solution, respectively. Combining the effects of the electrolysis parameters, thermodynamic calculations, emission spectra, and product characterization, the mechanism of the formation process was analyzed. As a result, pure NiO was be obtained from a 0.4 M NiSO4  solution at 150 V and 10 min, and Ni powder was produced from a solution of 0.15 M NiSO4 –0.05 M NiCl2  with the operating electrode immersed 1 mm into the electrolyte. The formation of NiO was attributed to the oxidation of Ni formed in the reaction via Ni + H2 O → NiO + H2 ; pure Ni was generated via reduction by electrons and H radicals formed under these mild experimental conditions, which can avoid further oxidization to NiO. Furthermore, the temperature at the discharge area was estimated to be >1300 K, and the temperature at the thin layer beneath the discharge area, where NiO was produced, was between 771 and 1300 K. However, the temperature at the thin layer around the discharge area was <771 K during the preparation of Ni. Therefore, the mechanism for the formation of NiO and Ni was proposed according to the deviation in temperature. Multi-electrode electrolysis was used for the preparation of NiO and Ni, and the particle size distribution of NiO and Ni was 0.26–24.5 μm and 0.1–24.67 μm, respectively.